The Experiences of Students in the Modular and Online Learning: A Phenomenological Study - Cortes, Venus M.; Omongos, May Gaselle C.; Quevedo, Jerry Mae G.; Villarin, Michelle; J. Yaun, Karlene Kate; V. Segarra, Marry Mael (International Journal of Humanities and Education Development (IJHED), 2022)
This study aimed to determine the specific experiences of university students in terms of cognitive, social, emotional, and adversity skills in an online or modular mode of learning. The study utilized a phenomenology research design, and a semi-structured interview was conducted. Participants in the study were composed of students enrolled in online and modular learning who were asked to share their experiences elaborately. The analysis revealed that despite the differences in the learning modalities, the students similarly experienced the same significant adjustments and academic challenges. These experiences include the lack or limited access to information, concerns about the accessibility of the learning opportunities, lack of economic resources, time management concerns, communication with professors and classmates, and self-motivation and coping mechanisms. As an intended outcome, a feasible distance learning blueprint composed of possible courses of action that can be taken to achieve a more effective and feasible distance learning setup is made.